Prevalence of Gastrointestinal Infection among International Travellers Returning to Canada - Margaret L Russell; Edgar J Love; Larissa KF Temple (Canadian Journal of Infectious Diseases)
Objective: To describe the prevalence of parasitic and bacterial gastrointestinal infection (excluding enterotoxigenic Escherichia coli) among international travellers attending the International Travel Clinic at The University of Calgary.